IMPLEMENTATION OF ISLAMIC EDUCATION CURRICULUM MANAGEMENT BASED ON PESANTREN LOCAL WISDOM IN THE ERA OF DISRUPTION - Effendy, Moh Hafid; Putikadyanto, Agus Purnomo Ahmad; Rizam, Masyithah Maghfirah (re-JIEM (Research Journal of Islamic Education Management), 2024)
This research is motivated by the development of Islamic religious education at Madrasah Aliyah Pondok Pesantren Mambaul Ulum Bata-Bata, where the curriculum patterns have become increasingly diverse over time. The purpose of this study is to describe the implementation of Islamic education curriculum management based on the local wisdom of the pesantren. A qualitative approach with a phenomenological type is used. Data was collected through interviews, observations, and documentation. Data analysis was conducted through the stages of reduction, data display, and conclusion drawing/verification. The results of the study show that the curriculum is implemented through the stages of planning, curriculum implementation, structured program arrangements, assignment of teaching duties, and curriculum evaluation or assessment. Meanwhile, the subjects programmed by the pesantren are integrated into the learning process at Madrasah Aliyah, consisting of two majors: Science and Social Studies, including Science, Taruna, Research, Regular, and Intensive classes.